Cells from the hematopoietic lineage are only present transiently during healing in a mouse model of non-severe burn injury - Rea, Suzanne (Stem Cell Res Ther, 2015)
INTRODUCTION: The aim of our study is to identify the contribution of hematopoietic-derived cells to burn-wound healing in a non-severe injury. There are many conflicting reports of the contribution of bone marrow-derived cells to wound healing and whether these are hematopoietic or mesenchymal in origin. The role of hematopoietic lineage cells is investigated in this study in the context of the response to burn injury. METHODS: Transgenic mice expressing the LacZ reporter gene in all cells of the hematopoietic lineage underwent a non-severe full-thickness burn injury (8 % of total body surface area). Wounds were assessed for LacZ-positive cells at days 7, 14, and 28 post-injury by using whole-mount staining. Cells were also cultured from the wounds at each time point and analysed for expression of fibroblast and myofibroblast markers. RESULTS: At day 7, positive cells were identified in the wounds representing the inflammatory response. Some dermal cells were also identified at this early stage. At day 14, positive cells were also identified and were cultured from the wound tissue samples. However, by day 28, no positive cells could be detected or cultured from the healed wound tissue. Isolated LacZ-positive cells did not express collagen 1 or α-smooth muscle actin proteins, indicating that they had not differentiated into dermal fibroblast-type cells. CONCLUSIONS: In this model of burn injury, hematopoietic lineage cells were present in the healing wound only transiently and did not appear to contribute to the long-term scar population. This is in contrast with reports demonstrating that fibrocytes contribute a long-term sustained population in scar tissue. This work demonstrates that in a non-severe burn injury model there is a sustained transient contribution of hematopoietic cells to the healed wound. Further characterisation of the types and extent of wounding required to establish a long-term hematopoietic response will be important in determining future cell-based therapies.